Comparison of Patients Monoinfected with Hepatitis C Virus and Coinfected with Hepatitis B/C in the Amazon Region of Brazil - Regiane M. A. Sampaio; Paola Eduarda F. Dantas; Maria Inês C. da Silva; Joseane R. da Silva; Patrícia F. Nunes; Amanda C. Gomes; Luisa C. Martins (Viruses, 2022)
Hepatitis B and C are the most common causes of liver disease worldwide. The two infections share many similarities such as a global distribution, the same routes of transmission, hepatotropism, and the ability to cause chronic infection. The consequences of HBV/HCV coinfection are still being studied. The aim of this study is to describe and compare the epidemiological and laboratory profile and the degree of hepatic fibrosis between HCV-monoinfected and HBV/HCV-coinfected patients in the Brazilian Amazon region. ELISA tests were used for the investigation of HBV and HCV serological markers, and molecular tests were used for the detection and genotyping of these viruses. Additionally, transaminases were measured, and a FibroScan was performed for the analysis of liver function. A total of 328 patients with HCV participated in the study. The serological prevalence of HCV/HBV coinfection was 10.77%. A comparison of risk factors between the monoinfected and coinfected groups showed that illicit drug use, sharing sharp instruments, and tattooing/piercing are significantly associated with coinfection. The monoinfected patients had a higher HCV load than the coinfected patients. A viral interaction was observed in this study in which the presence of a coinfection with HBV appears to influence HCV replication. Further studies are necessary to better understand this interaction.